Esthesioneuroblastoma metastasis to the breast: A case report and review of the literature - Noppadol Larbcharoensub (2018)
Metastasis to the breast from an extramammary malignant neoplasm, including esthesioneuroblastoma, is uncommon. The present study describes a rare case of sinonasal esthesioneuroblastoma, Hyams' histologic grade 2, Kadish's stage C, T4N0M0, in a 30-year-old female. The patient underwent a radical ethmoidectomy with external beam radiotherapy, followed by chemotherapy including five cycles of cisplatin and etoposide. One year after the initial diagnosis, the patient presented to the hospital with the chief complaint of a rapidly enlarging lump in the right breast. A fine needle aspiration was performed and immunocytochemistry revealed a metastatic esthesioneuroblastoma. The patient received palliative chemotherapy and radiotherapy; however, the patient developed a local recurrence with systemic metastasis and succumbed to the disease seven months later.